ZYBT1, a potent, irreversible Bruton's Tyrosine Kinase (BTK) inhibitor that inhibits the C481S BTK with profound efficacy against arthritis and cancer. Issue 4 (13th August 2020) - Ghoshdastidar, Krishnarup; Patel, Hoshang; Bhayani, Hitesh; Patel, Ankit; Thakkar, Kinjal; Patel, Dinesh; Sharma, Manoranjan; Singh, Jaideep; Mohapatra, Jogeswar; Chatterjee, Abhijit; Patel, Dipam; Bahekar, Rajesh; et al.
Abstract: Bruton's tyrosine kinase (BTK) plays a central and pivotal role in controlling the pathways involved in the pathobiology of cancer, rheumatoid arthritis (RA), and other autoimmune disorders. ZYBT1 is a potent, irreversible, specific BTK inhibitor that inhibits the ibrutinib‐resistant C481S BTK with nanomolar potency. ZYBT1 is found to be a promising molecule to treat both cancer and RA. In the present report we profiled the molecule for in‐vitro, in‐vivo activity, and pharmacokinetic properties. ZYBT1 inhibits BTK and C481S BTK with an IC50 of 1 nmol/L and 14 nmol/L, respectively, inhibits the growth of various leukemic cell lines with IC50 of 1 nmol/L to 15 μmol/L, blocks the phosphorylation of BTK and PLCγ2, and inhibits secretion of TNF‐α, IL‐8 and IL‐6. It has favorable pharmacokinetic properties suitable for using as an oral anti‐cancer and anti‐arthritic drug. In accordance with the in‐vitro properties, it demonstrated robust efficacy in murine models of collagen‐induced arthritis (CIA) and streptococcal cell wall (SCW) induced arthritis. In both models, ZYBT1 alone could suppress the progression of the diseases. It also reduced the growth of TMD8 xenograft tumor. The results suggested that ZYBT1 has high potential for treating RA, and cancer.